Is waveform worth it? A comparison of LiDAR approaches for vegetation and landscape characterization. Issue 1 (29th November 2015) - Anderson, Karen; Hancock, Steven; Disney, Mathias; Gaston, Kevin J.
Abstract : Light Detection and Ranging (LiDAR) systems are frequently used in ecological studies to measure vegetation canopy structure. Waveform LiDAR systems offer new capabilities for vegetation modelling by measuring the time‐varying signal of the laser pulse as it illuminates different elements of the canopy, providing an opportunity to describe the 3D structure of vegetation canopies more fully. This article provides a comparison between waveform airborne laser scanning (ALS) data and discrete return ALS data, using terrestrial laser scanning (TLS) data as an independent validation. With reference to two urban landscape typologies, we demonstrate that discrete return ALS data provided more biased and less consistent measurements of woodland canopy height (in a 100% tree covered plot, height underestimation bias = 0.82 m;sd = 1.78 m) than waveform ALS data (height overestimation bias = −0.65 m;sd = 1.45 m). The same biases were found in suburban data (in a plot consisting of 100% hard targets e.g. roads and pavements), but discrete return ALS were more consistent here than waveform data (sd = 0.57 m compared to waveformsd = 0.76 m). Discrete return ALS data performed poorly in describing the canopy understorey, compared to waveform data. Our results also highlighted errors in discrete return ALS intensity, which were not present with waveform data. Waveform ALS data therefore offer an improved method for measuring the three‐dimensional structure of vegetation systems, but carry a higher data processing cost. New toolkits for analysing waveform data will expedite future analysis and allow ecologists to exploit the information content of waveform LiDAR. Abstract : Waveform LiDAR carries information about 3D canopy structure, but at a processing cost when compared to more widely used discrete return LiDAR. This article compares the information content and accuracy of waveform versus discrete return LiDAR using urban ecology as an exemplar. We show that waveform LiDAR outperforms discrete return LiDAR for describing complex 3D canopy structure.